Development of a new bombesin analog radiolabeled with lutetium-177: in vivo evaluation of the biological properties in Balb-C mice - Pujatti, P.B.; Santos, J. S.; Massicano, A. V. F.; Mengatti, J.; De araújo, E. B. (Cellular and Molecular Biology, 2010)
In this work we describe the first results of radiolabeling with lutetium-177 (177Lu) and in vivo biodistribution and pharmacokinetics studies in normal Balb-c mice of a new bombesin analog (BEFG2) – DOTA-Phe-X-BBN(6-14), where X is a spacer of two aminoacids. Bombesin (BBN) is an amphibian analog of human gastrin releasing peptide (GRP). Development of radiolabeled BBN derivatives as agents for diagnostic imaging and systemic radiotherapy has increased considerable because of the observation that GRP receptors (GRPr) are over-expressed in a variety of human tumor cells, such as prostate tumor cells. 177Lu-labeled peptides are attractive due to the excellent radiophysical properties and commercial availability of the radiometal. BEFG2 was successfully labeled with high yield and kept stable for more than 96 hours at 2-8º C and 1 hour in human plasma. Data analysis obtained from the in vivo studies showed that the amount of BEFG2 present in plasma decreased rapidly and became almost undetectable at 60 min p.i., indicating rapid peptide excretion, which is performed mainly by renal pathway. In addition, biodistribution and single photon emission tomography showed low abdominal accumulation of 177Lu-DOTA- Phe-X-BBN(6-14), indicating that this analog is a potential candidate for tumors target therapy.